2020
DOI: 10.1007/s00382-020-05547-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting controls on Congo Basin evaporation at the two rainfall peaks

Abstract: Evaporation is a crucial driver of Congo Basin climate, but the dynamics controlling the seasonality of basin evaporation are not well understood. This study aims to discover why evaporation on the basin-wide average is lower at the November rainfall peak than the March rainfall peak, despite similar rainfall. Using 16-year mean LandFlux-EVAL data, we find that evaporation is lower in November than March in the rainforest and the eastern savannah. The ERA5-Land reanalysis, which effectively reproduces this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…On the other hand, Burnett et al (2020) calculated basin-scale ET in the Congo using water-balance methods, positing that increased radiation, as well as the availability of soil moisture, can explain increased ET in the spring: Higher direct photosynthetically active radiation (PAR) fractions combined with higher net solar radiation increase water use efficiency, while increased terrestrial water storage increases the amount of water available for transpiration. Crowhurst et al (2020), using global climate models, also calculated ET over a similar domain and found that it was higher in the spring rainy seasons compared to the fall rainy season. They attributed changes in leaf area index and vapor pressure deficit to changes in transpiration between the spring and fall rainy season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Burnett et al (2020) calculated basin-scale ET in the Congo using water-balance methods, positing that increased radiation, as well as the availability of soil moisture, can explain increased ET in the spring: Higher direct photosynthetically active radiation (PAR) fractions combined with higher net solar radiation increase water use efficiency, while increased terrestrial water storage increases the amount of water available for transpiration. Crowhurst et al (2020), using global climate models, also calculated ET over a similar domain and found that it was higher in the spring rainy seasons compared to the fall rainy season. They attributed changes in leaf area index and vapor pressure deficit to changes in transpiration between the spring and fall rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…10.1029/2020JG006024 7 of 14 Figure 4b shows the contributions of ET and MFC to precipitation within our Congo domain, as indicated by ET/P and MFC/P. ET/P shows consistently high values throughout the year and MFC/P is always lower than that of ET/P (e.g., Burnett et al, 2020;Crowhurst et al, 2020). These data support our conclusion that there is a larger relative contribution of ET to the moisture for the spring versus fall rainy seasons.…”
Section: Precipitation and Dmentioning
confidence: 99%
“…The ERA5-Land reanalysis data set, containing 50 climate variables and covering all land areas of the world, can accurately reflect climate changes of the past few decades with a relatively high temporal and spatial resolution. Therefore, this dataset has been used increasingly to study long-term climate change in areas where observational data is scarce [18]. Here, we retrieved temperature and total precipitation data with a monthly temporal resolution and a time range of 1981-2020 in ERA5-Land from the European Centre for Medium-Range Weather Forecasts (ECMWF) (https://www.ecmwf.int/, accessed on 3 October 2020).…”
Section: Meteorological Datamentioning
confidence: 99%
“…Recycling ratios have been estimated in the 25-50% range (Pokam et al 2012;Dyer et al 2017;Sori et al 2017). Crowhurst et al (2021) note that basin-wide evaporation is lower in boreal fall than in boreal spring despite a similarity in precipitation due to lower leaf area indices and vapor pressure deficits in the southern rainforest.…”
Section: Introductionmentioning
confidence: 99%